2022
DOI: 10.1038/s41598-022-25464-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule inhibitor of human Drp1

Abstract: Mitochondrial dynamin-related protein 1 (Drp1) is a large GTPase regulator of mitochondrial dynamics and is known to play an important role in numerous pathophysiological processes. Despite being the most widely used Drp1 inhibitor, the specificity of Mdivi-1 towards human Drp1 has not been definitively proven and there have been numerous issues reported with its use including off-target effects. In our hands Mdivi-1 showed varying binding affinities toward human Drp1, potentially impacted by compound aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Rosdah et al identified a novel small molecule inhibitor of Drp1 (Drp1i27) that could directly bind to the human isoform 3 of Drp1 and increase the cellular networks of fused mitochondria in a dose-dependent way without any effects in Drp1 knock-out cells ( Rosdah et al, 2022 ). It showed cytoprotective potentials in human fibroblasts exposed to oxidative stress, HL-1 cells with ischemia-reperfusion damage, and human iPSC-derived cardiomyocytes with doxorubicin-induced cytotoxicity ( Rosdah et al, 2022 ). Thus Drp1i27 might be a promising alternative to Mdivi1 for the inhibition of Drp1 .…”
Section: Discussionmentioning
confidence: 99%
“…Rosdah et al identified a novel small molecule inhibitor of Drp1 (Drp1i27) that could directly bind to the human isoform 3 of Drp1 and increase the cellular networks of fused mitochondria in a dose-dependent way without any effects in Drp1 knock-out cells ( Rosdah et al, 2022 ). It showed cytoprotective potentials in human fibroblasts exposed to oxidative stress, HL-1 cells with ischemia-reperfusion damage, and human iPSC-derived cardiomyocytes with doxorubicin-induced cytotoxicity ( Rosdah et al, 2022 ). Thus Drp1i27 might be a promising alternative to Mdivi1 for the inhibition of Drp1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, caution must be exercised in utilizing these interventions since many molecules have multiple cellular functions and their effects are context dependent. For example, the effect of Mdivi-1, a chemical inhibitor of Drp1, upon I/R injury is dose and context dependent [ 148 , 222 ]. Myocardial ischemia without reperfusion activates not only conventional mitophagy but also alternative mitophagy in the heart [ 152 ].…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, Drpitor1 is an analogue of ellipticine, a known DNA intercalator, and its applicability beyond oncology has yet to be fully explored. DRP1i27 is a human DRP1 isoform 3 binder with modest affinity binding to GTPase site of DRP1 . The DRP1 inhibitors previously reported by Mitobridge were selective uncompetitive inhibitors of GTPase activity and served as unique tool compounds for exploring the roles of mitochondrial division in cells and assessing the potential therapeutic utility .…”
mentioning
confidence: 99%
“…DRP1i27 is a human DRP1 isoform 3 binder with modest affinity binding to GTPase site of DRP1. 11 inhibitors previously reported by Mitobridge were selective uncompetitive inhibitors of GTPase activity and served as unique tool compounds for exploring the roles of mitochondrial division in cells and assessing the potential therapeutic utility. 12 However, these compounds did not exhibit a significant mitochondrial morphology change in cells, which limited its application.…”
mentioning
confidence: 99%
See 1 more Smart Citation